RAQUEL DE QUEIROZ AND THE 1930s: THE MULTIFEMALE REPRESENTATIONS IN “O QUINZE” (REMUNOM, 2025)
The present study addresses the multiple representations of the feminine in O Quinze, by Rachel de Queiroz, through its female characters, with a particular focus on Mocinha and Conceição, reflecting on the places relegated to women and the different roles they occupy. Our objective is to identify the social critiques made by Rachel de Queiroz through these characters, as well as to analyze the representative function each of them assumes within a patriarchal society marked by the 1915 drought. The article will be developed based on texts that discuss the second generation of Brazilian Modernism, addressing regionalism and the history of droughts in the Northeast, with emphasis on that of 1915. Our reflections are grounded in readings on the 1915 drought and on social and gender issues that help reveal the construction of female roles and identities that were socially reflected in the decade in question. This study aims to demonstrate that Rachel de Queiroz’s work, in addition to its great literary relevance, presents important social and historical perspectives for readers’ reflection. To this end, we draw on studies by Bosi (2006), Luís Bueno (2015), among other authors who discuss perspectives of the 1930 Modernist generation, as well as historiographical research used to contextualize the 1915 drought.